2019
DOI: 10.1051/mattech/2019007
|View full text |Cite
|
Sign up to set email alerts
|

An estimation of the amount of dissipated alloy elements in special steel from automobile recycling

Abstract: According to the concept of a circular economy, further promotion of reuse and recycling might aid in closing the loop. However, material recycling may cause various types of material losses due to thermodynamic limitations and product complexity. In this study, we focused on automobile engines and their reuse, with the aim of quantifying the amount of dissipated steel alloy and its constituent elements (nickel and chromium) from the engine recycling process. We also elaborated upon their dissipation paths by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…and assembled engine are major shipment auto parts in the market for reused and rebuilt auto parts. Our preliminary results [27] showed that reuse had nearly the same effects as recycling on the reduction of material losses, but achieved the extension of product's service life. A detailed analysis would contribute to clarify not only the positive effects but also the limitations of remanufacturing of auto parts.…”
Section: Circulation System Designed To Retain Added Valuementioning
confidence: 73%
“…and assembled engine are major shipment auto parts in the market for reused and rebuilt auto parts. Our preliminary results [27] showed that reuse had nearly the same effects as recycling on the reduction of material losses, but achieved the extension of product's service life. A detailed analysis would contribute to clarify not only the positive effects but also the limitations of remanufacturing of auto parts.…”
Section: Circulation System Designed To Retain Added Valuementioning
confidence: 73%